Modelling and simulation for die casting mould filling process using Cartesian cut cell approach. (August 2015) - Bi, C.; Guo, Z.; Xiong, S.
<x content-type="archive" xml:space="preserve">Abstract</x> A three-dimensional simulation model based on the Cartesian cut cell approach was developed to improve the computational accuracy and grid configuration at the domain boundary for die casting mould filling process. The finite volume method and Gaussian transformation were used to solve the governing equations for cut cells at the boundaries, while the finite difference method was used for internal orthogonal cells. The surface areas of the cut cells of all of the topological structures were sorted and calculated to discretise the equations. The model was verified by simulating the filling process in two die casting moulds. Results of the numerical simulation agreed well with those of water analogy experiments. By matching the physical boundary with the cut cell approach, the proposed model significantly improved the accuracy of the simulation as well as the smoothness of the domain boundary description.